Molluscum contagiosum/Juvenile xanthogranuloma. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2019)
Molluscum contagiosum is the most frequent virus skin disorder in children. Juvenile xanthogranuloma is a frequent benign neoformation of the first years of life. These are two very different disorders. However, at its onset juvenile xanthogranuloma before it undergoes xanthomization can mimic molluscum contagiosum.